Replies to Commentators on The Concept of Argument: Clarifying Themes, Answering Questions, Settling Objections - Wohlrapp, Harald R. (Informal Logic, 2017)
The paper provides a series of responses to the papers published in Vol. 37, No. 3, of this journal that explored the ideas in Harald Wohlrapp’s The Concept of Argument (2014), where arguing is understood as the theoretical or theory-forming activity that can be found in research of all kinds. Thus, the approach taken focuses on the validity of theses. This approach is clarified further as the author considers points raised by his commentators and provides answers and, where necessary, corrections.